El presupuesto público y la toma de decisiones en la Municipalidad Distrital de Yaquerana 2023 - Santillan Torres, Belisario (2025)
The purpose of this study was to identify the relationship between public spending and decision-making in the Yaquerana District Municipality during 2023. An applied quantitative approach was used, with a non-experimental, explanatory design. The sample consisted of 53 municipal employees, who responded to questionnaires validated through content analysis, achieving a Cronbach's alpha reliability coefficient of 0.794 for the public budget and 0.822 for decision-making. In conclusion, a strong relationship was found between both variables, with a Spearman correlation coefficient of 0.686 and a significance level of p < 0.01, indicating a notable strong positive relationship.